The Role of Sharia Fintech Based on Maqashid Sharia Perspective - Widiastuty, Tri (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2022)
In recent years, both conventional and Islamic financial technology (fintech) have begun to develop. Although the number of Shariah fintech is not as many as the conventional one, its presence should be taken into account. As this fintech service develops, there are also many risks and challenges faced in its practice. Therefore, the researcher is interested in raising the topic of Shariah fintech, which is associated with the maqashid al-shariah perspective. The objective of this study is to determine the development of Shariah fintech in Indonesia from its emergence to the present, to determine the role of Shariah fintech in the perspective of maqashid al-shariah, and to determine obstacles in the development of Shariah fintech. The research method used in this study is descriptive analysis method with a qualitative approach. The researcher performed a literature study to collect data from various sources that support the researcher’s chosen topic, i.e., Shariah fintech associated with maqashid al-shariah. In general, Shariah fintech has fulfilled the principles of maqashid al-shariah. However, there are elements that need to be more strengthened. An example is the need for a governing regulation that separates Shariah fintech from conventional fintech regulation. This is because there are very different crucial elements and principles between these two types of fintech.